Avaliação de investimentos em sistemas integrados de gestão empresarial - Wantroba, Elaine (2007)
The systems ERP (Enterprise Resource Planning) had a considerable growth in the last years, impelled by the technological innovation and the market competition. We live in a time where the technology became a competitive and strategic differential inside the organizations. For that reason, every investment in Information Tecnology - IT, needs to be very well appraised and aligned to the businesses of the companies, helping the growth, the development and even, the survival in the current market. Among the advantages that the computerized systems offer, there are the agility in the information, data integration, reduction of personnel's costs, improvement in the productive processes, among others. However, the acquisition of IT assets, especially integrated systems of administration, it is considered still expensive and difficult to adapt in the companies reality, turning difficult to justify the return obtained with such investments. Usually, the traditional indicators of return make unfeasible the projects of IT. It appears, then, the need to justify such projects for other ways. In this study, it will be discussed and presented methodologies that seek to evaluate the investments in ERP systems, considering the tangible and intangible benefits of return, as well as the strategic alignment. Although no methodology is universally accepted it is important the knowledge of them, so It will be possible to enlarge the discussion on the theme. A diagnosis of a real case of implantation of ERP will be accomplished, in an industrial group, here denominated as Alpha, evidencing which were the chosen criteria for making decisions about the choice of the system, how was the procedure of the implantation of the system and how the managers evaluate the process, in two years of implementation. Methodologies for evaluation of investments in ERP systems will be exhibited too, based in the existent literature.